Correlation between total pressure losses of highly loaded annular diffusers and integral stage design parameters. (27th August 2018) - Mimic, Dajan; Jätz, Christoph; Herbst, Florian
Abstract : Diffusers convert kinetic flow energy into a rise in static pressure. This pressure recovery is the primary aerodynamic design objective for exhaust gas diffusers in power-generating steam and gas turbines. The total pressure loss is an equally important diffuser design parameter. It is strongly linked to the pressure recovery and the residual kinetic energy of the diffuser outlet flow. A reduction benefits the overall thermodynamic cycle, which requires the adjacent components of a diffuser to be included in the design process. This paper focuses on the total pressure losses in the boundary layer of a highly loaded annular diffuser. Due to its large opening angle the diffuser is susceptible to flow separation under uniform inlet conditions, which is a major source for total pressure losses. However, the unsteady tip leakage vortices of the upstream rotor, which are a source of losses, stabilise the boundary layer and prevent separation. Experiments and unsteady numerical simulation conducted show that the total pressure loss reduction caused by the delayed boundary layer separation exceed the vortex-induced losses by far. This flow interaction between the rotor and diffuser consequently decreases the overall total pressure losses. The intensity of the tip leakage vortex is linked to three rotor design parameters, namely work coefficient, flow coefficient and reduced blade-passing frequency. Based on these parameters, we propose a semi-empiric correlation to predict and evaluate the change in total pressure losses with regards to design operating conditions.